Spatial and Seasonal Variability of Long-Term Sea Surface Temperature Trends in Aegean and Levantine Basins - Saracoglu, Fevziye Ayca; Aydogan, Burak; Ayat, Berna; Saracoglu, Kebir Emre (SPRINGER BASEL AG, 2021)
This study aims to estimate the spatial variability of the long-term trends of Sea Surface Temperature (SST) in the Eastern Mediterranean Sea including the Aegean Sea for 39 years between 1982 and 2020. Two datasets consisting of in-situ daily mean SSTs provided by the Turkish State Meteorological Service for the 12 stations located along the Aegean and Levantine coasts of Turkey and gridded daily mean Optimum Interpolation Sea Surface Temperature version 2.1 (OISSTv2.1) data obtained from the National Centers for Environmental Information (NCEI) of the United States National Oceanic and Atmospheric Administration (NOAA) are used for this aim. The trend of change in SST is computed using a non-parametric Theil-Sen estimator methodology. The significance of trends is computed using the Mann-Kendall test. As well as the long-term trends of monthly mean SST, the trends of monthly minimum and maximum SSTs are analyzed to reveal the long-term variations of extreme SSTs. It is concluded that there is a statistically significant upward trend within the study area. The annual basin-averaged upward trends of monthly mean, minimum, and maximum SSTs are estimated as 0.039 degrees C/year, 0.043 degrees C/year, and 0.037 degrees C/year, respectively. Coastal in-situ data present different characteristics for the Aegean Sea and the Levantine Basin. Aegean Sea stations show that the annual maximum SST has a higher rate of upward trend than the annual mean and minimum SSTs, while measurements from the Levantine Basin show minimum SST values increasing at a greater rate than both the annual means and maximums. Analysis of in-situ data at 12 stations provides statistically significant trends between 0.024 degrees C/year and 0.055 degrees C/year, 0.025 degrees C/year and 0.093 degrees C/year, and 0.031 degrees C/year and 0.071 degrees C/year for annual mean, annual minimum, and annual maximum SSTs, respectively. Seasonal analysis of the monthly mean SST trends shows that the highest upward trend occurs in August at the Dikili station (Aegean Sea) with a rate of 0.110 degrees C/year. SST in the study area is significantly affected by the Atlantic Multidecadal Oscillation (AMO), Eastern Atlantic (EA), and East Atlantic/West Russia (EA/WR) indices.
Keywords: Sea surface temperature; Trend; Aegean Sea; Eastern mediterranean Sea; Spatial variability; Seasonal variability; In-situ data; ASIAN SUMMER MONSOON; MEDITERRANEAN SEA; INTERANNUAL VARIABILITY; LEVEL; OSCILLATION; SATELLITE; FLOWS; GULF; Geochemistry & Geophysics